ANALISIS PENGARUH JUMLAH PERSEDIAAN BERAS DAN HARGA BERAS TERHADAP PEMBENTUKAN INFLASI DI PROVINSI DKI JAKARTA - Rafli Rahman Farizi; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The high price of rice spread to an increase in the price of goods. The inelasticity of the production of foodstuffs includes the growth rate of food production, which is slower than the rate of population growth and per capita income, resulting in the price of foodstuffs increasing more than the increase in the prices of other goods. It can lead to demands for an increase in employee wages, resulting in increased production costs because the total production costs have increased. This study aims to analyze the causal relationship between the amount of rice supply and the price of rice in DKI Jakarta Province, the causal relationship between rice prices and inflation in DKI Jakarta Province, and the causal relationship between the amount of rice supply and inflation in DKI Jakarta Province. The results showed 1) there is a two-way causality or reciprocal causality from the amount of rice supply and the price of rice; 2) the price of rice has a significant effect on inflation but inflation does not have a significant effect on the price of rice, so there is only one-way causality where only the price of rice affects inflation; 3) rice supply has no significant effect on inflation, and inflation does not have a significant effect on the rice supply variable so that there is no causality between the two variables. Further research can carry out research with similar variables over a longer period and use a wider range of variables.